Bilateral superior semicircular canal dehiscence: bilateral conductive hearing loss with subtle vestibular symptoms. Issue 3 (12th March 2020) - Pereira, Diogo; Leonardo, Abílio; Duarte, Delfim; Oliveira, Nuno
Abstract : Superior semicircular canal dehiscence is caused by a bone defect on the roof of the superior semicircular canal. The estimated prevalence when unilateral varies between 0.4% and 0.7% and is still unknown when bilateral. Patients may present with audiologic and vestibular symptoms that may vary from asymptomatic to disabling. We report a case of a 72-year-old Caucasian woman presented to otolaryngology department reporting imbalance, bilateral pulsatile tinnitus, hypoacusis while being very sensitive to certain sounds. Physical examination was unremarkable, except for the Rinne test that was negative in both sides. The patient underwent an audiometry revealing a mild bilateral conductive hearing loss. A temporal bone CT scan was performed which evidenced bilateral superior semicircular canal dehiscence. Cervical vestibular evoked myogenic potentials and electrocochleography confirmed diagnosis. Although rare, superior semicircular canal dehiscence shall be considered in conductive hearing loss with vestibular symptoms.